Low Filtering Method for Noise Reduction at Text to Speech Application - Sutanti, Putu Asri Sri; Mastrika Giri, Gst. Ayu Vida (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
Technological developments have greatly encouraged various researchers to develop several studies in the IT field. One branch of research in the IT field is sound synthesis. Some text-to-speech applications, are usually quite difficult to form and are less flexible in replacing existing types of sound. In addition, sometimes accent or how someone speaks is not well represented, so it is quite difficult to form a text-to-speech application by using the desired sound like user voice or other sounds. From the above problems, this research propose an application that can change text into sound or text-to-speech which is more flexible and in accordance with the wishes of the user. From the results of testing that has been done, this system has an accuracy of 70%.